The Effect of Cooperative Learning Intentionally Structuring Model on Self-Disclosure and Self-Awareness in Physical Education Learning at School - Stiadi, Dendy; Ma'mun, Amung; Juliantine, Tite (Universitas Pendidikan Indonesia, 2020)
Physical education is one of the subjects at schools that can make a significant contribution to studentsâ€™ interpersonal aspect and social. One of the main aspects in developing a change in attitude is self-disclosure and self-awareness. The purpose of this study was to find out how influential the cooperative learning intentionally structuring model on self-disclosure and self-awareness in Physical Education learning at school. The method used in this study was an experimental method with a pretest-posttest control group research design. The sample in this study were 60 students of class 10 (X) from SMK N 12 Bandung divided into 2 groups by using purposive sampling techniques. The instrument used to measure self-disclosure was ESDS (emotional self disclosure scale). Meanwhile, to measure self-awarness, the self awareness scale was used. Data analysis process used SPSS version 21 with Paired Sample T-Test for hypothesis testing. The results of the analysis and calculation of the data revealed that there were significant changes between the cooperative learning intentionally structuring learning model group and the control group. It showed that giving an explanation, or intentionally structuring, to the experimental group during physical education learning could affect the increase in the experimental group far above the control group.Â AbstrakPendidikan jasmani merupakan salah satu mata pelajaran di sekolah yang dapat memberikan kontribusi signifikan terhadap siswa antar pribadi dan pembangunan social ). Salah satu yang utama dari pengembangan perubahan sikap yaitu keterbukaan diri dan kesadaran diri. Tujuan dalam penelitian ini untuk mengetahui seberapa berpengaruh model pembelarajan cooperative learning intentionaly structuring terhadap keterbukaan diri dan kesadaran diri Â dalam pembelajaran penjas di sekolah. Metode yang digunakan dalam penelitian ini adalah experiment dengan desain penelitian pretest-posttest control group design. Sampel dalam penelitian ini berjumlah 60 siswa kelas 10 (X) di SMK N 12 Bandung yang di bagi kedalam 2 kelompok dengan mengunakan tehnik purposive sampling. Instrument yang digunakan menggunakan Instrument emotional self disclosure scale (ESDS) dan Instrument self awareness scale. Analisis data menggunakan SPSS versi 21 dengan pengujian hipotesis mengunakan Paired Sample T-Test. Hasil analisis dan perhitungan data mengungkapkan bahwa terdapat perubahan yang signifikan antara kedua kelompok model pembelajran cooperative learning intensionaly structuring dan kelompok control, dengan memberi penjelasan atau intentionally structuring kelompok eksperimen saat pembelajaran pendidikan jasmani sehingga mendapat peningkatan jauh di atas kelompok control.